The Impact of CEO Power on Financial Reporting Readability: Exploring the Moderating Influence of Earnings Performance and Corporate Governance - Hassan Fatahi Nafchi; Mohammad Joodaki; Zeynab Mansoorian (بررسی‌های حسابداری و حسابرسی)
Objective Annual financial and non-financial reports play a crucial role in enhancing public understanding and facilitating communication with stakeholders. Organizations employ various strategies, including managing the tone and readability of their reports, to shape perceptions among their audience and shareholders. These efforts aim to encourage desirable performance and present a positive image of the organization's performance. Therefore, this study aims to investigate the impact of CEO power on financial reporting readability, considering the moderating role of profitability and corporate governance. Methods This study employs an applied approach with an inductive methodology. Multiple regression analysis using panel data is utilized to examine the research hypotheses. In this research, necessary theoretical information in the field of research was collected using a comprehensive literature review. Then, the necessary information for model estimation was collected. Accordingly, the sample comprises data from 82 companies listed on the Tehran Stock Exchange spanning the years 2011 to 2021, covering 11 years. Results The results of the first hypothesis of the research indicate that the power of the CEO has a significant negative effect on financial reporting readability. Additionally, the results of the second hypothesis showed that firm profitability exacerbates the adverse impact of CEO power on financial reporting readability. Furthermore, the results of the third hypothesis indicate that corporate governance, as a moderating factor, does not significantly influence the relationship between CEO power and financial reporting readability. Conclusion Based on the Agency Theory and the Emotional Management Theory, the first hypothesis posits that powerful managers have personal interests and tend to disclose less, manipulated, or ambiguous information. The results of the second hypothesis also indicate that when firms perform significantly weaker than their peers in terms of profitability, management seeks to impair the analytical and processing abilities of users by using unstructured and disorderly textual narratives in annual reports, increasing the volume of pages, disclosing in footnotes, and using ambiguous sentences and words. Also, the results of the third hypothesis show that corporate governance cannot limit the negative impact of powerful CEO's motivations to manipulate the readability of corporate financial reports. These findings highlight the adverse impact of CEO power on financial reporting readability. It is anticipated that these insights will aid policymakers, including the Tehran Stock Exchange, in gaining a deeper understanding of CEOs' influence on financial reporting clarity. This understanding may prompt firms to adhere to guidelines, such as those implemented by the US Securities and Exchange Commission. These guidelines evaluate annual reports based on readability, aiming to control and mitigate opportunistic managerial behavior. Additionally, ranking annual reports based on readability can enhance corporate disclosure and transparency efforts.